New Business Model For Creative Agency Through Influencer Marketing - Rezi Muhamad Taufik Permana; M. Malik Akbar Rohandi; Yudha Dwi Nugraha (Universitas Islam Bandung, 2021)
ABSTRACTInfluencer Marketing is seen as one of the best strategies to bring in potential customers when using social media marketing by leveraging the masses of Influencers. The purpose of this study is to analyze the phenomenon of influencer marketing, business models and decision making in the use of influencers in marketing activities for creative agency business people. In this study, we will analyze the social relationships of individuals or groups because influencer marketing can be an appropriate reference group. This study uses secondary data contained in books, white papers, journals, articles which is the basis for a literature review, while primary data uses direct surveys with 200 respondent to social media active users. From the results of this study, it can be concluded that influencers have a significant role in the business processes of creative agencies. Where influencers who have quite significant followers and the variety of content they create make it attractive to consumers.Keywords : Influencer Marketing, Electronic Word of Mouth, Social Media Marketing. ABSTRAKPemasaran Influencer dipandang sebagai salah satu strategi terbaik untuk mendatangkan pelanggan potensial saat menggunakan pemasaran media sosial dengan memanfaatkan massa Influencer. Tujuan dari penelitian ini adalah untuk menganalisis fenomena influencer marketing, model bisnis dan pengambilan keputusan dalam penggunaan influencer dalam kegiatan pemasaran bagi para pelaku bisnis creative agency. Dalam penelitian ini, kami akan menganalisis hubungan sosial individu atau kelompok karena influencer marketing dapat menjadi kelompok referensi yang tepat. Penelitian ini menggunakan data sekunder yang terdapat dalam buku, white paper, jurnal, artikel yang menjadi dasar dari literature review, sedangkan data primer menggunakan survey langsung dengan 200 responden pengguna aktif media sosial. Dari hasil penelitian ini dapat disimpulkan bahwa influencer memiliki peran yang signifikan dalam proses bisnis agensi kreatif. Dimana influencer yang memiliki followers cukup signifikan dan variasi konten yang mereka buat membuatnya menarik bagi konsumen.Kata kunci : Influencer Marketing, Electronic Word of Mouth, Social Media Marketing.